2019
DOI: 10.1039/c8cc08803a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient hydrogen evolution of platinum via tuning the interfacial dissolved-gas concentration

Abstract: We present a facile perfluorooctanesulfonate-modulation strategy with a precisely controlled dissolved-gas concentration at the electrode/gas/electrolyte interface for enhanced HER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…102,130 However, when a second phase appears in the form of bubbles on or near the electrodes, they will continue to grow as the dissolved gases diffuse from the electrolyte, reducing the supersaturation of products in the electrolyte which again disturbs the equilibrium towards the products, ultimately reducing the concentration overpotential. 103,131,132,133 A recent study has shown the decoupling the concentration potential from the ohmic and activation by introducing superhydrophobic pits surrounded by a ring shaped microelectrode. Bubbles preferentially nucleated on these hydrophobic sites, preventing the masking of the electrocatalytic area and in consequence removing completely their effect on the kinetic overpotential and significantly the ohmic overpotential.…”
Section: Bubble Effects On Concentration Overpotentialmentioning
confidence: 99%
“…102,130 However, when a second phase appears in the form of bubbles on or near the electrodes, they will continue to grow as the dissolved gases diffuse from the electrolyte, reducing the supersaturation of products in the electrolyte which again disturbs the equilibrium towards the products, ultimately reducing the concentration overpotential. 103,131,132,133 A recent study has shown the decoupling the concentration potential from the ohmic and activation by introducing superhydrophobic pits surrounded by a ring shaped microelectrode. Bubbles preferentially nucleated on these hydrophobic sites, preventing the masking of the electrocatalytic area and in consequence removing completely their effect on the kinetic overpotential and significantly the ohmic overpotential.…”
Section: Bubble Effects On Concentration Overpotentialmentioning
confidence: 99%
“…After galvanostatic tests for 1500 s, the ECSA for CFPS‐Pt dropped by 11.6 %, whereas a substantial loss of 16.5 % in ECSA was observed for pure Pt. This result shows CFPS did not cause any significant loss of active surface area‐instead, it slowed down the surface deactivation, which should be a result of the electrostatic repulsion between CFPS and positively charged Pt surface during HzOR . These results indicate the effective exposure of active sites during hydrazine oxidation with the modulation of CFPS.…”
Section: Figurementioning
confidence: 99%
“…Heptadecafluorooctancesulfonic acid potassium (PFOS) is used as the surfactant in this study since it does not participate in the electrochemical reaction and can reduce the overpotential by lowering hydrogen dissolution in the electrolyte. 59 Fig. 5a shows bubble generation at j = 300 mA cm −2 and different flow rates.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PFOS reduces the dissolved hydrogen concentration close to the electrode. 59 This leads to a lower concentration overpotential due to hydrogen supersaturation at the electrode surface. 60 As a result, the required potential for the reactions decreases at constant current densities as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%